(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
Simultaneous interpreting is one of the most cognitively demanding forms of language mediation, requiring interpreters to listen, process, translate, and produce speech almost simultaneously. Beyond linguistic competence, successful simultaneous interpreting depends heavily on the interpreter’s ability to navigate pragmatic and cultural dimensions of communication. Pragmatic meanings, including implicatures, speech acts, politeness strategies, and contextual references, often present significant challenges because they are deeply embedded within specific socio-cultural environments. Similarly, cultural elements such as idioms, humor, historical references, customs, and values frequently resist direct translation, increasing the risk of misunderstanding and communication breakdown. This study investigates the pragmatic and cultural difficulties encountered in simultaneous interpreting and examines the strategies employed by interpreters to overcome these obstacles. Using a qualitative research design, examples from international conferences, diplomatic discourse, and intercultural communication settings are analyzed to identify common challenges and effective coping mechanisms. The findings reveal that pragmatic ambiguity, culture-bound expressions, humor, politeness norms, and institutional references constitute major sources of difficulty. Furthermore, experienced interpreters tend to employ strategies such as explicitation, adaptation, omission, reformulation, and contextualization to preserve communicative intent. The study highlights the importance of cultural competence and pragmatic awareness in interpreter training programs. It concludes that successful simultaneous interpreting requires not only linguistic proficiency but also extensive intercultural knowledge and pragmatic sensitivity. These findings contribute to the growing body of research on interpreting studies and provide practical recommendations for interpreter education and professional practice.